2021
DOI: 10.20960/nh.03440
|View full text |Cite
|
Sign up to set email alerts
|

High nutritional risk using NUTRIC-Score is associated with worse outcomes in COVID-19 critically ill patients

Abstract: High nutritional risk using NUTRIC-Score is associated with worse outcomes in COVID-19 critically ill patientsAsociación entre el riesgo nutricional evaluado a través de NUTRIC-Score y los desenlaces clínicos en pacientes en estado crítico con

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 10 publications
1
10
0
6
Order By: Relevance
“…In this study, univariate analysis revealed that the risk of death increased with the risk of malnutrition according to NRS2002 (HR = 1.18). Osuna-Padilla et al showed that nutritional risk in mechanically ventilated ICU patients was related to an increased risk of death (OR = 2.4, and was found in 66% of patients [36]. A similar result was reported by Zhang et al, where nutritional risk was found in more than 60% of hospitalised patients.…”
Section: Discussionsupporting
confidence: 60%
“…In this study, univariate analysis revealed that the risk of death increased with the risk of malnutrition according to NRS2002 (HR = 1.18). Osuna-Padilla et al showed that nutritional risk in mechanically ventilated ICU patients was related to an increased risk of death (OR = 2.4, and was found in 66% of patients [36]. A similar result was reported by Zhang et al, where nutritional risk was found in more than 60% of hospitalised patients.…”
Section: Discussionsupporting
confidence: 60%
“…Zhang et al [ 15 ], in a retrospective study conducted in China, reported that a large proportion of critically ill COVID-19 patients had a high nutritional risk (61%) as revealed by their mNUTRIC-Score. High-nutritional-risk scores were similarly prevalent (66%) in an observational study conducted in the central region of Mexico [ 17 ]. In both studies, the mNUTRIC-Score was able to independently predict the risk of death at 28 days.…”
Section: Discussionmentioning
confidence: 99%
“…The adjusted score was called the modified NUTRIC (mNUTRIC)-Score. During the COVID-19 pandemic, an increased prevalence of high nutritional risk has been reported in other studies of critically ill patients using the mNUTRIC-Score [ 15 17 ].…”
Section: Introductionmentioning
confidence: 93%
“…A maior parte dos estudos seguiram delineamento observacional. Destes, a maioria (n = 5) se refere a pesquisas de coorte retrospectiva e ambidirecional, com dados de adultos hospitalizados durante um período da pandemia de COVID-19 (Formenti et al, 2021;Osuna-Padilla et al, 2021;Larrazabal Jr. et al, 2021;Wu et al, 2021;Lin et al, 2021). Também foi verificada a realização de estudo de intervenção (n = 1) (Watteville et al, 2020) e estudos longitudinais observacionais (n = 2) (Bedock et al, 2021;Nicolau et al, 2021).…”
Section: Fonte: Autores (2021)unclassified
“…Autores A utilização do escore de pontuação NUTRIC (Nutrition Risk in the Critically Ill Score) foi verificada em três estudos (Osuna-Padilla et al, 2021;Wu et al, 2021;Lin et al, 2021). O NUTRIC é um escore de risco nutricional para pacientes críticos desenvolvido e validado, especificamente, para pacientes em Unidades de Terapia Intensiva (UTI).…”
Section: Títulounclassified